Propósitos educacionais no meio on-line: o caso dos cursos de inglês gratuitos - Wissmann, Liane Dal Molin (2005)
A quick search through the Internet allows us to find an expressive number of free English courses, representing not only the possibilities that this new means of communication offers, but also the importance that this language took, mainly due to the cultural and economical domination exerted by the countries related to it. Thus, through this work, I try both investigate to what extent these courses manage to provide educational purposes by on-line means, and to identify the underlying teaching approaches observed in the corpus. Also, having as a starting point both the strictly cultural and social character of learning (Vygotsky, 1934: 117-131), and the assumption that negotiations involving the exchange of information through interaction help in the acquisition of a new language, I try to verify the nature of the interaction between teacher, student and content, related by the courses. The instrument used in the research was the checklist for evaluation of on-line language courses , proposed by Freire et al (2003: 245-276). It is divided into seven areas, likely to be found in any given interface, which constituted the categories of analysis of this work: contextual, technical, instructional, interactive, affective, evaluative and operational. The results show that a great part of these courses are based on behaviorist conceptions about teaching and learning a new language, which are implemented through the translation and grammar method. In general, the proposals that try to escape from this model are not able to organize themselves in terms of activities offered to the students. In regards to the kind of interaction provided, it is just rudimental or, according to Primo (2003: 1-16), a reactive interaction. Therefore, a great part of the on-line English courses analyzed are just repositories and/or virtual conveyors of information, corroborating Mason (1998) who argues that the most common model of courses is the one based on the content and, in which one can notice the migration to the internet of the contents previously available in the traditional classroom, with static contents, structured in pages on the web and with a low level of interaction. However, it is important to emphasize all of the courses analyzed have their own value, because they represent rehearsal about how to teach through this new way, willing to be improved and mainly, an alternative way to socialize information.